Interacciones Familiares y Autoestima: Un Estudio entre Estudiantes de Secundaria. - Madrid-Gómez, Karina Eddmy; Herrera-Aponte, Milca Betsabé; Arias-Huánuco, Jesús Mery; Zevallos-Parave, Ysabel; Camposano-Córdova, Alvaro Ignacio; LLancari-Choccelahua, Rosa Belinda (Editorial Grupo AEA, 2024)
The objective of this book was to determine the family social climate and self-esteem in high school students in Huancavelica, methodologically the research was applied type, non-experimental design of correlational and descriptive level, the study population was 138 high school students aged 15 and 17 years from the school “Francisca Diez Canseco de Castilla” in Huancavelica of probabilistic sampling with a survey technique of measurement scale that includes ninety items, ten sub dimensions and three dimensions of reliability between 0. 88 and 0.91, using the SPSS program. The results indicate a positive relationship of low intensity between Family Social Climate and Self-Esteem, with correlation coefficient 0.29. It is concluded that the social climate helps to improve the students' self-esteem.